Edukasi Akuntansi Dan Peningkatan Efektifitas Pelaporan Keuangan Bumdes Berbasis Excel For Accounting (EFA) - Rama Gita Suci; Zul Azmi; Evi Marlina; Adriyanti Agustina Putri; Siti Rodiah; Intan Putri Azhari (Asosiasi Dosen Akuntansi Indonesia, 2021)
The business run by the Citra Permai Village-Owned Enterprise (BUMDes) is the sale of fertilizers for the village community, where this business is quite smooth and makes it very easy for the local community. BUMDes Citra Permai is still doing manual bookkeeping. Bookkeeping which is carried out for each transaction only uses cash in and cash out and also calculates the remaining inventory of goods also manually. From the results of these service activities there are limitations in the capacity of human resources, namely the understanding of making financial reports and inadequate support for computerized technology. With the problems found, the method used is training and mentoring using EFA-based Excel to motivate and inspire to operationalize EFA-based bookkeeping. This service is important in the hope that there will be an increase in knowledge about BUMDes management to the Village Government and BUMDes managers, increase the competence and understanding of BUMDes managers in regulating the purchase of goods and sales, calculating physical inventory, compiling BUMDes financial reports independently, and implementing financial administration